KONTINUITAS DAN DISKONTINUITAS PENDIDIKAN PONDOK PESANTREN AL-ASY’ARIYYAH, KALIBEBER, WONOSOBO (1832-2022) - Robingun Elsyam (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
This article aims to reveal the dimensions of continuity and discontinuity of education at the al-Asy'ariyyah Islamic boarding school Kalibeber Wonosobo (1832-2022), by synthesizing the Islamic education system that runs in each leadership period. This paper is a historical research using Harry J. Benda's theory of continuity and change, through the stages of: topic selection, heuristics, verification, interpretation, and historiography. The results of the study show that the continuity of the education system at the al-Asy'ariyyah Islamic boarding school has been maintained until now by emphasizing the Qur'an as the center of study. The discount is part of the development which is determined by the dynamics and changing times. The implication of the research is that the essence of the teachings of the Koran is a patron that must be preserved so that it can relate to the needs of the times. Research contributes to the development of Islamic boarding schools that are adaptive to the constellation of changes.